Hubungan Intensitas Menonton Film Animasi Upin & Ipin dengan Nilai Moral Anak Usia 5-6 Tahun - Rosalita, Selvia; Herpratiwi, Herpratiwi; Nopiana, Nopiana (Journal of Early Childhood Education (JECE), 2024)
This study aims to determine the relationship between the intensity of watching Upin & Ipin animated films and the moral values of children aged 5-6 years in Pesisir Selatan District, West Pesisir Regency. The type of research used is quantitative with the expos facto method and associative design. The research sample consisted of 75 children who were determined using simple random sampling technique. Data were collected through questionnaires given to parents to obtain variable x data and through direct observation of children to obtain variable y data. The collected data were then analyzed using the product moment correlation test formula after prerequisite tests such as normality test and linearity test. The results of hypothesis testing obtained a significance value between the intensity of watching Upin & Ipin animated films with children's moral values of 0.000 with an Alpha error rate of 0.05, so that it is stated that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The higher the intensity of children watching Upin & Ipin animated films, the higher the chance of moral values in children aged 5-6 years in the South coastal district of the West coast district.